Loggerhead sea turtle, Caretta caretta, presence and its exposure to floating marine litter in the Sardinia Channel and the Strait of Sicily: results from seven years of monitoring using ferry as platform of observation - ATZORI, FABRIZIO; CAROSSO, LARA; CADONI, NICOLETTA; FRAU, FRANCESCA; GARCÍA GUTIÉRREZ, MARÍA LEONOR; DE LUCIA, GIUSEPPE ANDREA; GREGORIETTI, MARTINA; PELLEGRINO, GIULIANA; LIUBARTSEVA, SVITLANA; LECCI, RITA; COPPINI, GIOVANNI; MAFFUCCI, FULVIO; et al. (Mediterranean Marine Science, 2021)
The loggerhead turtle is the most common sea turtle species in the Mediterranean Sea. Despite relevant research efforts, information of its distribution is still scarce, particularly in the open sea where they may be exposed to different threats among which marine litter is of great concern. Here we investigated the distribution of loggerhead turtles and floating marine macro litter (FMML) in the Sardinia Channel and Strait of Sicily, a key area of the central Mediterranean Sea, by using 7 years of data collected by experienced observers aboard passenger ferries along commercial routes. The high-risk exposure areas were identified and the influence of upper layer currents on turtle and FMML distribution was evaluated. Overall, loggerhead sighting rates were higher than those reported from other Mediterranean routes but the distribution of turtles within the study area was clearly heterogeneous and influenced by the surface circulation pattern. Summer sighting rates were significantly higher in the Sardinia Channel with respect to the Strait of Sicily. Analysis of the co-occurrence of FMML and loggerhead turtles identified a priority risk area in the central Sardinian channel where the large South-Eastern Sardinia Gyre acts as a trap for both animals and FMML. This study corroborates the effectiveness of using passenger ferries as platforms of observation to conduct systematic surveys of sea turtles and floating macro litter in offshore areas. Results highlighted the importance of the Sardinia Channel and Strait of Sicily for the loggerhead turtle and the areas of greater risk of exposure to the marine litter threat.